The transition to electric car changes of Indonesia automotive supplier component companies - Rabbani, Alif Nadhif; Muhammad Habiburrahman; Rahmat Nurcahyo (Komunitas Ilmuwan dan Profesional Muslim Indonesia (KIPMI), 2024)
The popularity of electric cars has risen significantly over the past years and create changes towards the Indonesia automotive industry. The increase in electric car popularity has made the automotive industry shift its focus towards electric cars that disrupt its industrial landscapes. Hence, efforts are needed to analyze the potential changes required by the current Indonesia automotive industry to accommodate the transition to electric cars. The study surveyed car manufacturers and component suppliers, analyzing their perceptions and assessing the importance of the electric car market. Data were gathered via online and on-site surveys and were subjected to descriptive statistical analysis, confirmatory factor analysis, and cluster analysis. Results indicated that successful market penetration of electric cars hinges on strategic decisions and effective coordination among stakeholders. Research and development, along with equipment modifications, are expected to increase, necessitating a streamlined supply chain to manage fluctuating demand. Close collaboration between component suppliers and car manufacturers is essential to sustain value-added operations.